Efficient Production of Fuel Ethanol via the Simultaneous Use of Distillery Stillage Biomass and Beet Molasses - Katarzyna Osmolak; Dawid Mikulski; Grzegorz Kłosowski (Energies)
The integrated production of ethanol fuel through the simultaneous use of various by-products and waste materials is an intriguing concept, as it maximizes the raw material potential while addressing the challenge of managing waste biomass from different technological processes. The efficient utilization of lignocellulosic waste depends on employing a pretreatment method that enhances the susceptibility of structural polysaccharides to hydrolysis. The aim of the study was to assess the possibility of the simultaneous use of corn stillage biomass and beet molasses as raw materials for the production of ethanol fuel. The research focused on optimizing the process conditions for the acid pretreatment of stillage biomass and the enzymatic hydrolysis of cellulose and evaluating the effectiveness of two fermentation strategies: SHF (Separate Hydrolysis and Fermentation) and SSF (Simultaneous Saccharification and Fermentation). The highest hydrolysis susceptibility was observed in biomass pretreated with 2% v/v H3PO4 for 30 min at 121 °C. The maximum glucose concentration of about 12 g/L (hydrolysis efficiency about 35.5%) was achieved even with the lowest enzyme dose, i.e., 7.5 FPU per gram of biomass. The yeast also showed high fermentation activity in media prepared from stillage biomass and molasses, producing about 50 g/L of ethanol regardless of the fermentation strategy used. The complete fermentation of carbohydrates assimilated by yeast confirmed the complementarity of the two raw materials used to prepare fermentation media, emphasizing the high potential of the proposed technological solution for ethanol fuel production.